KANK1 regulates paclitaxel resistance in lung adenocarcinoma A549 cells - Junyi Pu; Jianfeng Shen; Zihua Zhong; Ma Yanling; Jie Gao (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Paclitaxel (PTX), a tubulin-binding agent, is widely used and has shown good efficacy in the initial period of treatment for non-small cell lung cancer (NSCLC). However, the relatively rapid acquisition of resistance to PTX treatments that is observed in virtually all cases significantly limits its utility and remains a substantial challenge to the clinical management of NSCLC. The aim of this study was to identify candidate genes and mechanisms that might mediate acquired paclitaxel resistance. In this work, we established paclitaxel-resistant cells (A549-T) from parental cell lines by step-dose selection in vitro. Using methylation chip analysis and transcriptome sequencing, 43,426 differentially methylated genes and 2,870 differentially expressed genes are identified. Six genes (KANK1, ALDH3A1, GALNT14, PIK3R3, LRG1, WEE2), which may be related to paclitaxel resistance in lung adenocarcinoma, were identified. Among these genes, KANK1 exhibited significant differences in methylation and expression between cell lines. Since KANK1 plays an important role in the development of renal cancer and gastric cancer, we hypothesised that it may also play a role in acquired resistance in lung adenocarcinoma. Transient transfection of SiKANK1 significantly reduced the expression of KANK1, reducing apoptosis, increasing cell migration, and enhancing the tolerance of A549 cells to paclitaxel. KANK1 acts as a tumour suppressor gene, mediating the resistance of lung adenocarcinoma A549 to paclitaxel. The reduction of KANK1 expression can increase the paclitaxel resistance of non-small cell lung cancer and increase the difficulty of clinical treatment.